(untitled) (Revista de Crítica Literaria Latinoamericana, 2025)
This work recovers a minimal but essential personal anthology by José Antonio Mazzotti, still unpublished, to explore the art of some of the most important features of his general poetics: those that trace an aesthetic continuity and give particular substance to the baroque style that critics have identified in his poetry